Evolutionarily conserved features contribute to αβ T cell receptor specificity - Scott-Browne, James P. (2011)
αβ T cell receptors (TCRs) bind specifically to foreign antigens presented by major histocompatibility complex proteins (MHC) or MHC-like molecules. Accumulating evidence indicates that the germline-encoded TCR segments have features that promote binding to MHC and MHC-like molecules, suggesting co-evolution between TCR and MHC molecules. Here, we assess directly the evolutionary conservation of αβ TCR specificity for MHC. Sequence comparisons showed that some Vβs from distantly related jawed vertebrates share amino acids in their complementarity determining region 2 (CDR2). Chimeric TCRs containing amphibian, bony fish or cartilaginous fish Vβs can recognize antigens presented by mouse MHC class II and CD1d (an MHC-like protein), and this recognition is dependent upon the shared CDR2 amino acids. These results indicate that features of the TCR that control specificity for MHC and MHC-like molecules were selected early in evolution and maintained between species that last shared a common ancestor over 400 million years ago.